Candidemia in intensive care units over nine years at a large Italian university hospital: Comparison with other wards. - Sara Mazzanti; Lucia Brescini; Gianluca Morroni; Elena Orsetti; Antonella Pocognoli; Abele Donati; Elisabetta Cerutti; Christopher Munch; Roberto Montalti; Francesco Barchiesi (PLoS ONE)
Purpose Candidemia is an alarming problem in critically ill patients including those admitted in intensive care units (ICUs). We aimed to describe the clinical and microbiological characteristics of bloodstream infections (BSIs) due to Candida spp. in patients admitted to ICUs of an italian tertiary referral university hospital over nine years. Methods A retrospective observational study of all cases of candidemia in adult patients was carried out from January 1, 2010 to December 31, 2018 at a 980-bedded University Hospital in Ancona, Italy, counting five ICUs. The incidence, demographics, clinical and microbiologic characteristics, therapeutic approaches and outcomes of ICU-patients with candidemia were collected. Non-ICU patients with candidemia hospitalized during the same time period were considered for comparison purposes. Early (7 days from the occurrence of the episode of Candida BSI) and late (30 days) mortality rates were calculated. Results During the study period, 188/505 (36%) episodes of candidemia occurred in ICU patients. Cumulative incidence was 9.9/1000 ICU admission and it showed to be stable over time. Candida albicans accounted for 52% of the cases, followed by C. parapsilosis (24%), and C. glabrata (14%). There was not a significant difference in species distribution between ICU and non-ICU patients. With the exception of isolates of C. tropicalis which showed to be fluconazole resistant in 25% of the cases, resistance to antifungals was not of concern in our patients. Early and late mortality rates, were 19% and 41% respectively, the latter being significantly higher than that observed in non-ICU patients. At multivariate analysis, factors associated with increased risk of death were septic shock, acute kidney failure, pulmonary embolism and lack of antifungal therapy. The type of antifungal therapy did not influence the outcome. Mortality did not increased significantly over time. Conclusion Neither cumulative incidence nor crude mortality of candidemia in ICU patients increased over time at our institution. However, mortality rate remained high and significantly associated with specific host-related factors in the majority of cases.